An efficient semi-analytical method to extract the mode II bridging-traction law in ENF tests directly from the experimental load displacement data. (1st April 2022) - Cao, Tiancheng; Zhao, Libin; Wang, Linjuan; Wang, Kangkang; Gong, Yu; Zhang, Jianyu
Abstract: Large scale fiber bridging ahead of the crack tip of ENF specimen is one of the most common toughening mechnisms, leading to a significant resistance phenomenon on the fracture toughness. In order to account for the toughening effect of the fiber bridging to accurately model the delamination of composite laminates, a physically semi-analytical method is presented to determine the mode II bridging law with the assumption of linear form directly from the experimental load displacement curve. The method includes the deflection analysis of the ENF specimen based on the beam theory considering the closing force introduced by fiber bridging and the inverse method iteratively determining the bridging law parameters. To validate the proposed method, the identified bridging tractions by the current method are integrated in the traditional cohesive law to simulate the whole delamination propagation process of undirectional laminates with different materials and multidirectional laminates. Good agreements between the numerical results and experimental ones indicate the accuracy and the applicability of the current method. The major advantage of the proposed method is that it reduces the instructmentation needed in the delamination test and it can be adopted as an efficient method to investigate the delamination behaviour of specimens.